Cutting Tools
Patent Information
- Application Number
- JP2021029152
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-02-25
AI Technical Summary
【0015】 本発明に係る切削工具は、副硬質相の平均粒径を2.0μm以上、6.0μm以下とし、副硬質相の合計界面長に対する副硬質相-結合相粒界長の比率を9.0%未満とすることにより、耐塑性変形性が向上するため、連続旋削加工のような高負荷下での連続切削加工においても、長期の切削寿命を有するという顕著な効果を奏するものである。
Smart Images

Figure 0007643079000001 
Figure 0007643079000002 
Figure 0007643079000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a WC-based cemented carbide cutting tool using, as a tool base, a WC-based cemented carbide that exhibits excellent resistance to plastic deformation in continuous cutting (e.g., continuous turning) of alloy steels and the like (steel, stainless steel, Ni-based alloys, etc.). [Background technology]
[0002] WC-based cemented carbide has high hardness and toughness, and therefore WC-based cemented carbide tools and surface-coated WC-based cemented carbide tools using this alloy as a base exhibit excellent wear resistance and are known as cutting tools having a long life over long periods of use. However, in recent years, various proposals have been made to further improve the cutting performance and tool life of WC-based cemented carbide tools depending on the type of work material, cutting conditions, etc.
[0003] For example, Patent Document 1 proposes that in a cemented carbide alloy having a main hard phase mainly composed of tungsten carbide and a binder phase mainly composed of an iron group element (including cobalt, the cobalt content of which is preferably 8 mass % or more in the cemented carbide alloy), when the number of tungsten carbide particles is A and the number of tungsten carbide particles having one or less contact points with other tungsten carbide particles is B, by satisfying B / A≦0.05, the plastic deformation resistance of the cemented carbide alloy is improved, and as a result, the life of a WC-based cemented carbide tool is extended in wet continuous cutting of carbon steel and stainless steel.
[0004] In Patent Document 2, in a WC-based cemented carbide tool containing 10 to 13 mass% Co, a ratio of 2 to 8% Cr to Co, at least one of TaC and NbC in a range such that the total amount of TaC and NbC is 0.2 to 0.5 mass%, with the remainder being WC, and having a hardness of 88.6 HRA to 89.5 HRA, it is proposed that the ratio D80 / D20 of the WC cumulative grain size 80% diameter D80 to the cumulative grain size 20% diameter D20 in the area ratio on the polished surface is set to a range of 2.0≦D80 / D20≦4.0, D80 is set to a range of 4.0 to 7.0 μm, and the WC adhesion degree c is set to 0.36≦c≦0.43, thereby preventing adhesion of the workpiece and improving chipping resistance in cutting difficult-to-cut materials such as stainless steel.
[0005] In Patent Document 3, when the composition of the WC-based cemented carbide is expressed as WC-x mass %, Co-y mass %, Cr3C2-z mass %, VC, in a WC-based cemented carbide tool, the following conditions are satisfied: 6≦x≦14, 0.4≦y≦0.8, 0≦z≦0.6, (y+z)≦0.1x. In addition, the WC adhesion degree C of the WC-based cemented carbide is expressed as C=1-V b α When expressed as ·exp(0.391·L), the value of the binder phase volume fraction of the WC-based cemented carbide in this formula, V b is 0.11≦V b In addition, the value L of (standard deviation of WC particle size distribution) / (average WC particle size) is within the range of 0.3≦L≦0.7, and the coefficient α satisfies the value of 0.3≦α≦0.55. In this way, a WC-based cemented carbide tool has been proposed that has improved toughness and enhanced chipping resistance without reducing hardness and rigidity in cutting Al alloys, carbon steel, etc.
[0006] In Patent Document 4, when the length of the WC-WC adhesive interface in a WC-based cemented carbide tool is L1 and the length of the WC-Co adhesive interface is L2, R>(0.82-0.086×D)×(10 / V) It has been proposed that the thermal plastic deformation resistance and toughness of WC-based cemented carbide tools can be improved in cutting Ni-based heat-resistant alloys by satisfying the following equation. In addition, R = (L1) / ((L1)+(L2)) D: WC area average particle size (μm), which is in the range of 0.6≦D≦1.7. Here, the above D refers to the particle size of WC when the area ratio of WC is 50%. V: binder phase volume (vol%), which is in the range of 9≦V≦14.
[0007] Patent Document 5 proposes a WC-Co based cemented carbide part for cutting tools, which has a composition by weight consisting of Cr or / and Cr compounds: 0-4% (in terms of Cr), V or / and V compounds: 0-4% (in terms of V), TaC: 0-2%, TiC: 0-2%, N or / and N compounds: 0-1% (in terms of N), Co: 0.1-10%, WC and inevitable impurities: the remainder, and has a Co average thickness (CFP) of 0.06-30 nanometers, and is densified by applying a pressure of 3 atm to 200 atm using gas as a pressure medium in a part or the whole range of the temperature range of 900°C to 1600°C during heating during sintering. It is said that the toughness of this WC-Co based cemented carbide part, preferably an ultrafine grain low Co cemented carbide part having an average WC grain size of 1 μm or less and a CFP in the range of 0.06-30 nm, can be improved. Here, CFP is the average Co thickness (nm), The value was calculated from CFP=0.58*A / (100-A)*R, where A is Co (weight %) and 2R is WC average particle size (nm). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2016-20541 A [Patent Document 2] JP 2017-88999 A [Patent Document 3] JP 2017-148895 A [Patent Document 4] JP 2017-179433 A [Patent Document 5] Japanese Patent Application Publication No. 7-305136 Summary of the Invention [Problem to be solved by the invention]
[0009] According to the conventional WC-based cemented carbide tools proposed in the above Patent Documents 1 to 5, the cutting performance and tool characteristics of the WC-based cemented carbide tools are improved by controlling the number of contact points between WC-WC particles, the particle size of the WC, the degree of WC adhesion, or manufacturing conditions, etc. However, when the conventional tools are used in continuous cutting of steel, alloy steel, stainless steel, and the like, particularly in continuous cutting under high load such as continuous turning, the plastic deformation resistance of the base body is insufficient, and the occurrence of tool deformation and the like cannot be sufficiently suppressed, resulting in a problem that the tool reaches the end of its life. [Means for solving the problem]
[0010] In order to develop a WC-based cemented carbide tool that exhibits excellent resistance to plastic deformation in continuous cutting processes under high loads, such as continuous turning processes of steel, alloy steel, stainless steel, and the like, the present inventors have changed their viewpoint from that of conventional techniques and have conducted intensive research focusing on the grain boundary length and interface length related to the secondary hard phase of a WC-based cemented carbide consisting of a main hard phase, a secondary hard phase, and a binder phase, i.e., the length of the interface where a secondary hard phase contacts a main hard phase (hereinafter referred to as "secondary hard phase-main hard phase interface length"), the length of the grain boundary where a secondary hard phase contacts another secondary hard phase (hereinafter referred to as "secondary hard phase-secondary hard phase grain boundary length"), and the length of the interface where a secondary hard phase contacts a binder phase (hereinafter referred to as "secondary hard phase-binder phase interface length"), and have obtained the following findings. The WC-based cemented carbide according to the present invention comprises a main hard phase containing WC, a secondary hard phase containing a single carbide of Ti, Ta, Nb, Zr, Hf and V and / or a composite carbide of a plurality of the above elements, and a binder phase containing Co and / or Ni.
[0011] That is, in the WC-based cemented carbide tools shown in Patent Documents 1 to 4, improvements have been made mainly focusing on WC particles, and in the WC-based cemented carbide tool shown in Patent Document 5, improvements have been made mainly focusing on CFP. However, the present inventors have taken a different perspective from the conventional techniques and discovered that when the ratio of the "secondary hard phase-bonding phase interface length" to the sum of the "secondary hard phase-main hard phase interface length", the "secondary hard phase-secondary hard phase grain boundary length", and the "secondary hard phase-bonding phase interface length" (also referred to as the "total interface length of secondary hard phases") is 9.0% or more, the secondary hard phase-main hard phase interface and the secondary hard phase-secondary hard phase interface are insufficient, and a skeletal structure consisting of the main hard phase and the secondary hard phase cannot be satisfactorily formed. When a large load is applied at high temperatures, the skeletal structure collapses, causing significant plastic deformation and shortening the tool life.
[0012] Therefore, the inventors have addressed this problem by adjusting the component composition of the WC-based cemented carbide, using a coarse solid solution, and adjusting the mixing order of the binder phase to arrange the secondary hard phases having large crystal grain sizes so as to reduce contact with the binder phase. This makes it possible to reduce the ratio of 3) the secondary hard phase-binder phase interface length to the total length of the secondary hard phases, which is the total of 1) the secondary hard phase-main hard phase interface length, 2) the secondary hard phase-secondary hard phase grain boundary length, and 3) the secondary hard phase-binder phase interface length, to less than 9.0%, thereby solving the problem of the present invention, which is the deterioration of plastic deformation resistance.
[0013] The present invention has been made based on the above findings and is as follows. "(1) In a cutting tool made of WC-based cemented carbide having a WC-based cemented carbide as a substrate, The composition of the WC-based cemented carbide contains at least one of Co and Ni in an amount of 4.0% by mass or more and less than 10.0% by mass, Also, at least one selected from TiC, TaC, NbC, ZrC, HfC, and VC is contained in a total amount of 4.0 mass% or more and less than 12.0 mass%; Further, the alloy contains 0.0 mass% or more and less than 0.5 mass% of Cr3C2, The balance is composed of WC and unavoidable impurities. The average grain size of the secondary hard phase is 2.0 μm or more and 6.0 μm or less, A cutting tool made of WC-based cemented carbide, characterized in that the ratio of the interface length between a secondary hard phase and a binder phase to the total interface length of the secondary hard phases is less than 9.0%. (2) A surface-coated WC-based cemented carbide cutting tool, characterized in that a hard coating layer is formed on the cutting edge of the WC-based cemented carbide cutting tool according to (1) above."
[0014] The contents of TiC, TaC, NbC, ZrC, HfC, VC, and Cr3C2 in (1) and (2) above are values calculated as carbide equivalents of the amounts of Ti, Ta, Nb, Zr, Hf, V, and Cr measured on a longitudinal section of a WC-based cemented carbide cutting tool. In addition, in this specification, when a numerical range is indicated using "to", it means that the lower limit and upper limit of the numerical range are included. Effect of the Invention
[0015] The cutting tool according to the present invention has an average grain size of the secondary hard phases of 2.0 μm or more and 6.0 μm or less, and the ratio of the grain boundary length of the secondary hard phase - binder phase to the total interface length of the secondary hard phases is less than 9.0%, thereby improving the resistance to plastic deformation, and thus exhibits the remarkable effect of having a long cutting life even in continuous cutting processes under high loads, such as continuous turning processes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The composition of each component constituting the WC-based cemented carbide according to the present invention and the structure of the cemented carbide (binder phase, main hard phase, secondary hard phase) will be described below.
[0017] 1.WC-based cemented carbide composition The composition of the cemented carbide constituting the cutting tool of this embodiment is: Co and / or Ni, 4.0% by mass or more and less than 10.0% by mass, One or more of TiC, TaC, NbC, ZrC, HfC, and VC is 4.0 mass% or more and less than 12.0 mass%. Contains 0.0 mass% or more and less than 0.5 mass% of Cr3C2, The balance consists of WC and unavoidable impurities. The following explains each in order.
[0018] (1) Co, Ni Co and Ni are the main components of the binder phase in the WC-based cemented carbide. It is preferable that the cutting tool contains one or both of Co and Ni as the main components, and the total content of Co and Ni is 4.0 mass% or more and less than 10.0 mass% of the entire cutting tool. Here, the term "main component" refers to a composition in which either one or both of Co and Ni are contained in a total amount of 50 at % or more relative to all components forming the binder phase. The binder phase may contain at least one of Ti, Ta, Nb, Zr, Hf, and V. When these elements are present in the binder phase, they are presumed to be in a state of solid solution in the binder phase. Furthermore, the binder phase may contain W and C, which are components of the main hard phase, and other unavoidable impurities. The at% of Co and Ni can be determined by mirror-finishing any surface or cross section of the cemented carbide and subjecting the machined surface to fluorescent X-ray diffraction measurement.
[0019] (2)Cr3C2 Cr3C2 dissolves as Cr in Co, which forms the main binder phase, and inhibits the growth of the WC phase, which forms the main hard phase, refines the grain size of the WC phase, gives the WC-based cemented carbide a fine and uniform grain structure, and has the effect of increasing toughness and improving plastic deformation resistance. On the other hand, if the Cr3C2 content exceeds 5% relative to the Co content, this action may cause the precipitation of composite carbides of Cr and W, reducing toughness and becoming the starting point for the generation of chipping. In the present invention, Cr is not an essential component. However, since the upper limit of the Co content is less than 10.0 mass%, when Cr is added, the content is preferably less than 0.5 mass% in terms of Cr3C2 with respect to the entire cutting tool.
[0020] (3) TiC, TaC, NbC, ZrC, HfC and VC TiC, TaC, NbC, ZrC, HfC and VC are contained in the WC-based cemented carbide as main secondary hard phase forming components, and the total content of one or more of these components is 4.0 mass% or more and less than 12.0 mass%. When these carbides are present, it is preferable that the content of one or more compounds represented by MC is less than a maximum of 12.0 mass% based on the entire cutting tool, assuming that the carbide is a 1:1 bond between M (metal atom) and C. That is, if it is 12.0% by mass or more, the wear resistance becomes insufficient and agglomerates are easily formed, which become the starting point for the occurrence of chipping, so that it is preferable to keep the content in the range of less than 12.0% by mass. Furthermore, if the average grain size of the secondary hard phases formed by these carbides is less than 2.0 μm, the secondary hard phases are likely to slip between each other during cutting, resulting in insufficient resistance to plastic deformation and chipping. On the other hand, if the average grain size exceeds 6.0 μm, sufficient wear resistance cannot be obtained. Therefore, it is preferable to select the average grain size from the range of 2.0 μm or more and 6.0 μm or less.
[0021] The average grain size of these secondary hard phases is determined by mirror-finishing any surface or cross section of the cemented carbide, observing the machined surface at pixel size by electron backscatter diffraction (EBSD), determining the area of at least 300 secondary hard phases by image analysis, and calculating the diameter of a circle equal to the area, and averaging the diameters. For the mirror finishing, for example, a focused ion beam device (FIB device), a cross-section polisher device (CP device), or the like is used.
[0022] (4) WC WC is contained as a main hard phase forming component of the WC-based cemented carbide. The main hard phase may contain unavoidable impurities that are inevitably mixed in during the manufacturing process. If the average grain size of the main hard phase containing WC, which is the main hard phase forming element, is less than 0.2 μm, the main hard phases are likely to slip during cutting, and the plastic deformation resistance and chipping resistance are insufficient. On the other hand, if the average grain size exceeds 4.0 μm, sufficient wear resistance cannot be obtained. Therefore, it is preferable to select the grain size from the range of 0.2 μm or more and 4.0 μm or less. The average grain size of the main hard phases, like that of the secondary hard phases, is determined by mirror-finishing any surface or cross section of the cemented carbide, observing the machined surface at pixel size by electron backscatter diffraction (EBSD), determining the area of at least 300 main hard phases by image analysis, and averaging the diameters of circles equal to the areas. The mirror finishing is also similar in that a focused ion beam device (FIB device), a cross-section polisher device (CP device), etc. are used.
[0023] (5) Inevitable impurities As described above, the secondary hard layer, the main hard phase, and the binder phase may contain impurities that are inevitably mixed in during the manufacturing process, and the amount of such impurities is preferably 0.3% by mass or less, with the total mass of the cutting tool being 100%.
[0024] 2. Method for deriving the ratio of the interface length between the secondary hard phase and the bonding phase to the total interface length of the secondary hard phase The ratio of the interface length of the secondary hard phase to the total interface length of the secondary hard phase is derived, for example, by using an OIM Data Collection (OIM crystal orientation analyzer) manufactured by TSL, to simultaneously capture EBSD (Electron Back Scattered Diffraction) patterns and EDS (Energy Dispersive X-ray Spectroscopy) data.
[0025] Next, for each crystal grain, the EDS count values obtained from each measurement point inside the crystal grain corresponding to each element are averaged to obtain the EDS measurement value of each element of each crystal grain, and the composition of each crystal grain is derived from the obtained measurement value. From the EBSD pattern, crystal grains identified as HCP phase and containing 20 at% or more of W are WC grains, particles identified as FCC phase with a total content of Co and Ni of 50 at% or more are binder phases, and particles with a total content of Co and Ni less than 50 at% are secondary hard phases, and the total interface length of the secondary hard phase is the total length of the secondary hard phase-main hard phase interface length, the secondary hard phase-secondary hard phase grain boundary length, and the secondary hard phase-bonding phase interface length, and the secondary hard phase-bonding phase interface length is divided by the total interface length of the secondary hard phase to obtain the secondary hard phase-bonding phase interface length ratio. The observation field is set to have a size of 20 μm (vertical) × 70 μm (horizontal) and a pixel size of 40 nm (vertical) × 40 nm (horizontal).
[0026] Next, the WC-based cemented carbide tool according to the present invention will be specifically described with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0027] <WC-based carbide tool of the present invention> (a) Blend with raw powder As raw material powders, WC powder with an average particle size (d50) of 2.5 μm to 6.5 μm, and Co powder, Ni powder, Cr3C2 powder, TiC powder, TaC powder, NbC powder, ZrC powder, HfC powder, and VC powder, all of which have average particle sizes (d50) in the range of 1.0 to 3.0 μm, were prepared. First, among these powders, TiC powder, TaC powder, NbC powder, ZrC powder, HfC powder, and VC powder, which are carbides of secondary hard phase forming elements, were weighed out to obtain a predetermined composition, mixed for a long period of 24 hours in a ball mill, then heat treated in a vacuum at 1800°C for 4 hours, and then crushed in a ball mill for 1 hour to produce a coarse solid solution powder (see the column for solid solution powder in Table 1).
[0028] (b) Heating and sintering process Next, the obtained coarse solid solution powder was mixed with the WC powder and Cr3C2 powder, and wet-mixed at 600 RPM for 1 hour using an attritor. Co powder and Ni powder were then added to the attritor pot in which the powders were mixed, and mixed at 150 RPM for 10 minutes. The obtained slurry was dried and then press-molded at a pressure of 100 MPa to produce a powder compact. (See steps 1 to 10 of the present invention in Table 3.)
[0029] 1) Heating process First, in the temperature increase process from 1000°C, which is the solid-phase sintering temperature, to 1350°C, which is the sintering temperature, the temperature increase rate was increased to 40°C / min or more to suppress solid-phase sintering.
[0030] 2) Sintering process Next, after heating to 1350° C. or higher, sintering was carried out at 1350° C. to 1450° C. for 10 to 80 minutes under vacuum conditions of 0.1 Pa or less to obtain a WC-based cemented carbide sintered body. This sintering process allows the secondary hard phases with large crystal grain size to be positioned with reduced contact with the binder phase, and the ratio of the grain boundary length between the secondary hard phase and the binder phase to the total interface length of the secondary hard phase can be lowered, so that a strong skeletal structure consisting of the main hard phase and the secondary hard phase can be established, and excellent resistance to plastic deformation can be achieved.
[0031] Next, the obtained WC-based cemented carbide sintered body was machined and ground to have a shape of CNMG432MM, and cemented carbide substrates 1 to 10 shown in Table 4 (hereinafter referred to as inventive tool substrates 1 to 10) were produced.
[0032] ≪Comparative example WC-based carbide tool≫ For comparison, comparative cemented carbide substrates 1 to 8 (hereinafter referred to as comparative tool substrates 1 to 8) were prepared.
[0033] (a) Blend with raw powder As raw material powders, WC powder with an average particle size (d50) of 2.5 μm to 6.5 μm, and Co powder, Ni powder, Cr3C2 powder, TiC powder, TaC powder, NbC powder, ZrC powder, HfC powder, and VC powder, all of which have average particle sizes (d50) in the range of 1.0 to 3.0 μm, were prepared. Next, these prepared powders were mixed to obtain the composition shown in Table 2 to prepare sintering powder. The powder was wet mixed for 1 hour at a rotation speed of 600 rpm using an attritor, dried, and then pressed at a pressure of 100 MPa to produce a powder compact.
[0034] (b) Heating and sintering process Next, sintering was performed under the heating conditions and sintering conditions of comparative steps 1' to 8' shown in Table 3 to obtain a WC-based cemented carbide sintered body. The WC-based cemented carbide sintered body was then machined and ground to have a shape of CNMG432MM, thereby producing comparative example tool bases 1 to 8 shown in Table 5.
[0035] Next, for the cross sections of the cemented carbide of the tool bases 1 to 10 of the present invention and the comparative tool bases 1 to 8, the contents of each of the elements Co, Ni, Cr, Ta, Nb, Ti, Zr, Hf and V were measured using an electron microanalyzer (EPMA) over an entire field of view of 60 μm (vertical) × 90 μm (horizontal), with no overlapping between any of the ten fields of view, and the average values were taken as the contents of each component. The contents of the elements Cr, Ta, Nb, Ti, Zr, Hf and V were calculated in terms of carbide. Tables 4 and 5 show the average contents of each element.
[0036] Next, for the cross sections of the cemented carbide of the tool substrates 1 to 10 of the present invention and the comparative tool substrates 1 to 8, the EBSD patterns and the obtained EDS data were simultaneously captured using, for example, the OIM crystal orientation analyzer.
[0037] Next, for each crystal grain, the EDS count values obtained from each measurement point inside the crystal grain corresponding to each element were averaged to obtain the EDS measurement value for each element of each crystal grain, and the composition of each crystal grain was derived from the obtained measurement values.
[0038] Furthermore, among the crystal grains identified as FCC phases from the EBSD pattern, particles having a total Co and Ni content of 50 at% or more were defined as binder phases, and particles having a total Co and Ni content of less than 50 at% were defined as secondary hard phases. The total interface length of the secondary hard phase was defined as the total value of the secondary hard phase-main hard phase interface length, the secondary hard phase-secondary hard phase grain boundary length, and the secondary hard phase-binder phase interface length, and the secondary hard phase-binder phase interface length was divided by the total interface length of the secondary hard phase to obtain the secondary hard phase-binder phase interface length ratio. The observation field was set to have a size of 20 μm (vertical) × 70 μm (horizontal) and a pixel size of 40 nm (vertical) × 40 nm (horizontal).
[0039] [Table 1]
[0040] [Table 2]
[0041] [Table 3]
[0042] [Table 4]
[0043] [Table 5]
[0044] The above-mentioned tools 1 to 10 of the present invention and comparative tools 1 to 8 were subjected to the following wet continuous turning test while each tool was screwed to the tip of a tool steel bit using a fixing jig. Work material: JIS SUS304 (HB170) round bar, Cutting speed: 105m / min, Cutting depth: 2.2mm, Feed: 0.6mm / rev, Cutting time: 5 minutes, Uses wet water-soluble cutting oil. After the wet continuous cutting test, the amount of plastic deformation of the cutting edge was measured and the wear state of the cutting edge was observed. The amount of plastic deformation of the cutting edge was measured by drawing a line segment on the ridge where the rake face intersects with the flank face of the main cutting edge of the tool at a position sufficiently distant from the cutting edge, extending the line segment toward the cutting edge, and measuring the maximum distance between the extended line segment and the ridge line of the cutting edge (perpendicular to the extended line segment). When the amount of plastic deformation of the flank face was 0.04 mm or more, the wear state was determined to be cutting edge deformation. Table 7 shows the results of this test.
[0045] [Table 6]
[0046] In addition, hard coating layers having average thicknesses shown in Table 8 were formed by PVD or CVD on the cutting edge surfaces of the tools 1 to 4 of the present invention and the comparative tools 1 to 4, to produce surface-coated WC-based cemented carbide cutting tools 1 to 4 of the present invention (hereinafter referred to as "coated tools of the present invention") and comparative surface-coated WC-based cemented carbide cutting tools 1 to 4 of the comparative examples (hereinafter referred to as "coated tools of the comparative examples"). For each of the above-mentioned coated tools, the following wet continuous cutting test was carried out to measure the amount of plastic deformation on the flank of the cutting edge and to observe the state of wear of the cutting edge. Cutting conditions: Work material: JIS SUS304 (HB170) round bar, Cutting speed: 240m / min, Cutting depth: 2.0mm, Feed: 0.5mm / rev, Cutting time: 5 minutes, Uses wet water-soluble cutting oil. Table 9 shows the results of the cutting tests.
[0047] [Table 7]
[0048] [Table 8]
[0049] The test results shown in Tables 6 and 8 show that the tools of the present invention and the coated tools of the present invention exhibit excellent resistance to plastic deformation without the occurrence of fracture, whereas the comparative tools and the comparative coated tools have a short tool life due to the occurrence of fracture or plastic deformation. [Industrial Applicability]
[0050] As described above, the tool and the coated tool of the present invention exhibit excellent effects over long periods of use in heavy-duty continuous cutting, such as continuous turning of alloy steel, stainless steel, etc., and greatly contribute to extending the tool life.
Claims
1. A cutting tool made of a WC-based cemented carbide having a WC-based cemented carbide as a substrate, the WC-based cemented carbide has a composition containing at least one of Co and Ni in an amount of 4.0 mass% or more and less than 10.0 mass%; Also, at least one selected from TiC, TaC, NbC, ZrC, HfC, and VC is contained in a total amount of 4.0 mass% or more and less than 12.0 mass%, In addition, Cr 3 C 2 The content is 0.0 mass% or more and less than 0.5 mass%, and the balance is WC and unavoidable impurities, A WC-based cemented carbide cutting tool, characterized in that the average grain size of the secondary hard phase is 2.0 μm or more and 6.0 μm or less, and the ratio of the interface length of the secondary hard phase - binder phase to the total interface length of the secondary hard phase is less than 9.0%.
2. 2. A surface-coated WC-based cemented carbide cutting tool according to claim 1, further comprising a hard coating layer formed on a cutting edge of the WC-based cemented carbide cutting tool.
Citation Information
Patent Citations
Cemented carbide parts
JP1995305136A
Super hard alloy and cutting tool
JP2016020541A
Hard metal alloy, tool for cutting work using the same and insert for milling work
JP2017088999A
WC-based cemented carbide drill excellent in breakage resistance
JP2017148895A
WC-based hard metal alloy-made tool excellent in thermal resisting plastic deformation property
JP2017179433A